Health tourism as an engine for the development in the Department of Risaralda. Analysis period: 2000-2010 (2020)
The objective of this paper is whether the development of health tourism in the department of Risaralda in 2000-2010, increased the supply of health services and international trade potentiates the department. What is verified through a review of the literature produced by differents authors and institutions, so compared to later confront the claim through the analysis of similar cases both nationally and internationally. The results allowed to determine that this sector is in a nascent state in Risaralda, and exposed the flaws that prevent the progress made.